A COUNTERMEASURE AGAINST INTERNATIONAL DRUG CRIMES IN THE PERSPECTIVE OF INDONESIAN CRIMINAL LAW - Siringoringo, Poltak (Advances in Social Sciences Research Journal, 2020)
Circulation and use of narcotics and illegal drugs are massive crimes and can be categorized as "extraordinary crime" and become common enemies of this nation and even other nations in the world. Campaign and the formation of public opinion about the dangers of drugs must be done massively on all layers of society. This is part of the handling of drug crimes in Indonesia. Communities must be given a proper understanding of the negative effects of drugs both for users/users, dealers, who produce and store. This understanding starts from several phases namely what is the phase of drug prevention in society? What is the phase if it is already using drugs and putting drug users as victims? what is the phase of law enforcement against drug crimes? These phases must be campaigned on a massive scale so that people understand that things related to drugs have more negative impacts than positive effects. Collaboration with the international community in dealing with the dangers of drugs must also be carried out because drug trafficking networks to enter Indonesia cannot be separated through inter-state lines. Countries in the world must have the same perception and understanding that narcotics are a serious crime and need to be taken seriously by law enforcement agencies between countries.